2021
DOI: 10.1002/bio.4117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and self‐assembly of fluorescent fluorine‐containing liquid crystals

Abstract: S N Ar has been used to synthesize various functionalized derivatives of pentafluorobenzenes which are highly specific at the para position; and consequently are ideal for building calamitic (rod-like) liquid crystalline molecular systems. Here, we display the effectiveness of S N Ar chemistry as a convenient method toward the synthesis of fluorescent liquid crystalline perfluorinated comprising ethers and thioethers in excellent yields and high purity. In the current work, we describe the synthesis, self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Excellent yields (91-96%) for 4-alkoxy-4 0 -iodobiphenyls were obtained by treating the 4-hydroxy-4 0 -halobiphenyls with 1-haloalkane and potassium carbonate in dimethyl formamide (DMF) at room temperature. [16,17] Using diglyme as a solvent, with aryl iodide and potassium perfluorobenzoate, we were able to manufacture fluoroterphenyl at a high yield through Cu(I)-assisted decarboxylation. To facilitate a more efficient complexation between copper iodide and perfluorobenzoate anions, diglyme was used to create a coordination bond with potassium ions, as described previously by Liu et al [15] This reaction is very efficient, producing highquality yields.…”
Section: Chemistry and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent yields (91-96%) for 4-alkoxy-4 0 -iodobiphenyls were obtained by treating the 4-hydroxy-4 0 -halobiphenyls with 1-haloalkane and potassium carbonate in dimethyl formamide (DMF) at room temperature. [16,17] Using diglyme as a solvent, with aryl iodide and potassium perfluorobenzoate, we were able to manufacture fluoroterphenyl at a high yield through Cu(I)-assisted decarboxylation. To facilitate a more efficient complexation between copper iodide and perfluorobenzoate anions, diglyme was used to create a coordination bond with potassium ions, as described previously by Liu et al [15] This reaction is very efficient, producing highquality yields.…”
Section: Chemistry and Characterizationmentioning
confidence: 99%
“…Because of its sensitivity, it could be used instead of more expensive organometallic reagents in cross‐coupling procedures for the production of perfluorinated adducts. [ 16 ] The use of transition metals as catalysts in cross‐coupling processes for the preparation of perfluorinated chemicals has been the subject of more recent studies. However, these still have some issues such as limited selectivity, low yield, and side effects.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that all iodobiphenyl ethers have an absorption activity in the ultraviolet range. Those absorption peaks could be credited to the π–π * transitions [18, 19]. The absorbance band intensity increased with spreading the alkyl extent.…”
Section: Resultsmentioning
confidence: 99%
“…The organogelators were synthesized according to previous procedures. 38 Under ultraviolet light, aluminum plates coated with a thin layer of silica gel (60) were used to monitor the reaction progress by thin layer chromatography (TLC) (UV 254 ). Flash column chromatography was used to purify the produced chemicals using silica gel 60.…”
Section: Methodsmentioning
confidence: 99%
“…All solvents were of spectroscopic grade and obtained from Fluka and Sigma-Aldrich (Egypt). The organogelators were synthesized according to previous procedures . Under ultraviolet light, aluminum plates coated with a thin layer of silica gel (60) were used to monitor the reaction progress by thin layer chromatography (TLC) (UV 254 ).…”
Section: Methodsmentioning
confidence: 99%